Koneman's color atlas and textbook of diagnostic microbiology - Procop, Gary W. (Philadelphia : Wolters Kluwer Health, 2017)
"The founding objective of Koneman's Color Atlas and Textbook of Diagnostic Microbiology is to provide a clear exposition of procedures routinely employed in the laboratory identification of microbial agents causing infectious diseases"--Provided by publisher.
Introduction to microbiology : part I : the role of the microbiology laboratory in the diagnosis of infectious diseases : guidelines to practice and management -- Introduction to microbiology : part II : guidelines for the collection, transport, processing, analysis, and reporting of cultures from specific specimen sources -- Laboratory diagnosis by immunologic methods -- Molecular microbiology -- Medical bacteriology : taxonomy, morphology, physiology, and virulence -- The enterobacteriaceae -- The nonfermentative gram-negative bacilli -- Curved gram-negative bacilli and oxidase-positive fermenters : campylobacteraceae and vibrionaceae -- Miscellaneous fastidious gram-negative bacilli -- Legionella -- Neisseria species and moraxella catarrhalis -- Gram-positive cocci -- The gram-positive cocci : part I : staphylococci and Related gram-positive cocci -- The gram-positive cocci : part II : streptococci, enterococci, and the streptococcus-like bacteria-- Aerobic and facultative gram-positive bacilli -- Aerobic actinomycetes -- The anaerobic bacteria -- Antimicrobial susceptibility testing -- Mycoplasmas and ureaplasmas -- Mycobacteria -- Spirochetal infections -- Mycology -- Parasitology -- Diagnosis of infections caused by viruses, chlamydia, rickettsia, and related organisms.
Preceded by Koneman's color atlas and textbook of diagnostic microbiology / Washington C. Winn Jr. ... [et al.]. 6th ed. c2006.
Includes bibliographical references and index.
Keywords: Microbiological Phenomena; Microbiological Techniques